Atorvastatin effectiveness in dyslipidemia correction among coronary heart disease and arterial hypertension patients with high risk of cardiovascular complications - E. V. Minakov; N. I. Babenko; Yu. V. Popovskaya (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study the Russian atorvastatin generic (Liptonorm) effects on lipid metabolism in patients with coronary heart disease (CHD), essential arterial hypertension (EAH), and high risk of cardiovascular complications (CVC). Material and methods. In total, 30 patients (17 men, 13 women; mean age 52,37 years) with CHD (n=21), EAH (n=9), and high CVC risk were examined. Plasma levels of total cholesterol (TCH) were >5,2 mmol/l, low‑density lipoprotein CH, LDL‑CH ‑ >3,0 mmol/l. Lipid metabolism parameters and transaminase levels were measured at baseline, as well as after 2 and 4 weeks of Liptonorm treatment (10 mg/d). Results. After 4 weeks of the therapy, TCH and LDL‑CH levels were significantly reduced, by 22% from the baseline. Triglycerides (TG) concentration decreased to a lesser extent (8,8%); high‑density lipoprotein CH (HDL‑CH) and transaminase levels remained the same. Conclusion. Four‑week therapy with the Russian medication Liptonorm (10 mg/d) significantly reduced TCH, LDL‑CH levels, decreased TG concentration, without affecting HDL‑CH level. Liptonorm was safe, well tolerated, without any serious adverse effects. Patients ioetns regarded Lipronotm therapy regimen as “convenient”, that might increase their therapy compliance. Moreover, 90% of the patients regarded the medication price as “adequate” for their income levels.